PEMANFAATAN LIMBAH KULIT PISANG SEBAGAI PUPUK ORGANIK CAIR UNTUK PERTUMBUHAN SEMAI PALA (MYRISTICA FRAGRANS HOUTT) - Kotala Balgis; Ludia Siahaya; Febian F. Tetelay (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
The research was carried out at the Seed Nursery Forest Department, Faculty of Agriculture, Pattimura University for three month. This study aimed to determine the effect of the application of liquid organic fertilizer from Banana peel waste in increasing the growth of Nutmeg seedlings (Myristica fragrans Houtt) and to find out the dose of liquid organic fertilizer from Banana peel waste which gives the best results on the growth of Nutmeg seedlings (M. fragrans Houtt). The method used in this study was a completely randomized design (CRD) with 1 factor, consisting of 4 treatments, namely: A0 (control), A1 (100 ml), A2 (200 ml) and A3 (300 ml). The results showed liquid organic fertilizer from Banana peel waste could not increase the height growth and leaves number of Nutmeg seedlings, but it gave affect to diameter increasing of Nutmeg seedling. A3 treatment (300 ml) was the best treatment in terms of increasing diameter of nutmeg seedling stem.